DETECTION OF GENES RESPONSIBLE FOR HEAVY METALS RESISTANCE IN LOCALLY ISOLATED PSEUDOMONAS SPP. - Al-Sajad M. S.,; H.A.A. Alsalim, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
Plant growth-promoting rhizobacteria (PGPR) that can tolerate heavy metals, provide the basis for microbial inoculums showing heavy metals tolerance properties. This study was aimed to detect the heavy metal resistance genes in plant-growth-promoting Pseudomonas spp. isolated from many agricultural fields. The collected isolates were screened for their plant growth-promoting (PGP) traits, hydrolytic enzymes, Siderophore, ammonia, and indole-3-acetic acid (IAA). Then, subjected to concentrations of CuSO4, CdCl2, and ZnCl2 to determine the minimum inhibitory concentration (MIC). The DNA was extracted from the selected isolates then PCR test was achieved to detect copA, copB, and czcA genes, responsible for heavy metal resistance. Seventy Pseudomonas spp. isolates were obtained; 41 (58.57%), 6 (8.57%), and 15 (21.42%) isolate produced protease, cellulase, and pectinase, respectively. The isolates were positive for siderophore and ammonia production. However, 68 (97.14%) isolates have produced indole-3-acetic acid. Eight isolates were selected and identified as Pseudomonas aeruginosa using the Vitek 2 compact system. The isolates' resistance to heavy metals differed significantly. The isolate B49 had a higher resistance to CuSO4 (MIC = 3200 µg/ml) and ZnCl2 (MIC = 2600 µg/ml), while the isolate B66 recorded a higher resistance to CdCl2 (MIC = 1000 µg/ml).   copB, and czcA genes were detected in the eight P. aeruginosa isolates, while copA gene was detected in seven, except B69.